Medication Reconciliation: More than just a check. Issue 1 (June 2015) - Grindrod, Kelly; Tran, Poanna; Burns, Catherine
Medication reconciliation continues to be a poorly understood and poorly supported task. We conducted an exploratory study of medication reconciliation at 11 different health settings. Following the observations we used Cognitive Work Analysis to develop work domain models and decision ladder models. These models showed the complexity of medication reconciliation. Key challenges such as high demands for knowledge based behavior and inefficient information flows were identified. These areas suggest concrete ways of supporting the medication reconciliation task better.